Effects of Industry‐ and Region‐Specific Acquisition Experience on Value Creation in Cross‐Border Acquisitions: The Moderating Role of Cultural Similarity - Basuil, Dynah A.; Datta, Deepak K. (Journal of Management Studies, 2015)
ABSTRACTBased on a sample of 222 cross‐border acquisitions by US firms in the service sector, our study examines the effects of acquiring firms' prior cross‐border acquisition experience in the same industry and geographic region as the acquired firm on shareholder value creation. Using the BHAR (buy‐and‐hold abnormal returns) methodology, we find that higher levels of industry‐specific and region‐specific acquisition experience translate into greater shareholder value creation for acquiring firms in subsequent acquisitions. In addition, our results indicate that the effects of industry‐specific acquisition experience on acquisition performance are contingent on the level of cultural similarity between the acquiring and acquired firm countries, with the benefits of prior experience being greater in acquisitions undertaken in culturally similar countries. We also find that the moderating effects of cultural similarity on the relationship between industry‐specific acquisition experience and value creation are contingent on the level of prior region‐specific acquisition experience possessed by the acquiring firm.